Optimizing nursing care in phototherapy to improve treatment outcomes in neonatal jaundice management - Dong, Qian; Huang, Fan (Frontiers in Pediatrics, 2025)
ObjectiveNeonatal jaundice is a common condition affecting many newborns and often requires phototherapy to manage elevated bilirubin levels. This study aimed to evaluate the impact of optimized nursing care during phototherapy on treatment outcomes, investigating common nursing challenges and assessing whether enhanced interventions could accelerate recovery and improve overall effectiveness.MethodsA total of 106 neonates with jaundice who underwent phototherapy between January 1 and December 1, 2023, were randomly assigned to a control group and an intervention group, with 53 cases in each. The control group received standard nursing care, while the intervention group received targeted nursing interventions addressing phototherapy-related issues. Relevant clinical and laboratory data were collected from hospital records and nursing assessments, and treatment outcomes were compared between the two groups.ResultsThe intervention group exhibited significantly shorter times for symptom resolution, complete blood count recovery, first defecation, and meconium transition to yellow compared to the control group (P < 0.05). Moreover, total and indirect bilirubin levels were significantly lower in the intervention group than in the control group (P < 0.05), while direct bilirubin showed no significant difference. The rate of adverse nursing events was significantly lower in the intervention group (1.89%) compared to the control group (13.21%) (P < 0.05). Additionally, the quality-of-care score for the intervention group was significantly higher than that of the control group (P < 0.05).ConclusionsEnhancing nursing interventions for phototherapy-related issues in neonatal jaundice significantly improves therapeutic outcomes, accelerates recovery, and optimizes the effectiveness of phototherapy.